Lean - Emmanuel Sanchez Foundation; Asia Visions Media Foundation (Quezon City Asia Visions, 1988)
A documentary on the short political life of slain BAYAN leader, Lean Alejandro.
Editor, Lito Tiongson, Nonoy Regalado.
Keywords: Alejandro, Lean; Bagong Alyansang Makabayan -- Political activity; Biography